Bio-efficacy of fungicides against different fungal bioagents for tolerance level and fungistatic behaviour - and K.K. MISHRA, K.K. PANDEY*, P.K. PANDEY (Indian Phytopathology, 2006)
New generation fungicides are most frequently used in vegetable crops as seed treatment, soil drenching and foliar sprays. These fungicides have not been tested so far against Trichoderma spp. and the information is still lacking about the toxicity of these fungicides against different antagonists. Present studies revealed tolerance limit of the test fungicides by various biocontrol agents for compatibility. Complete inhibition of all the four species of Trichoderma is observed by tebuconazole and hexaconazole showing extremely toxic nature of the fungicide. Captan and propineb show tolerable growth up to 200 ).1grnl’ while azoxystrobin at 400 ).1grnl’. Among these fungicides mlÂ·1 azoxystrobin is less toxic and compatible up to 400).1gml’, Captan is fungistatic to T. harzianum and can be applied by keeping 2-3 days gap between the fungicide and bioagent as integration. Combination of soil treatment by captan followed by a few days seed treatment later with Trichoderma would be very safe and useful without any loss of Trichoderma. The level of the fungicidal toxicity varied among different biocontrol agents. Captan, propineb and azoxystrobin can be integrated between 200-400 ).1gml’ concentrations depending upon the species of Trichoderma. Pencycuron can be incorporated with Trichoderma even at a concentration of more than 400 ).1grnl’ for seed treatment in the integrateci management system.